Identification of Novel Selective Lysine‐Specific Demethylase 1 (LSD1) Inhibitors Using a Pharmacophore‐Based Virtual Screening Combined with Docking. (22nd December 2014) - Zhou, Chen; Kang, Di; Xu, Yungen; Zhang, Luyong; Zha, Xiaoming
<x xml:space="preserve">Abstract</x> Lysine‐specific demethylase 1 (LSD1) plays an important role in regulating the lysine methylation at residues K4 and K9 on histone H3. High levels of LSD1 expression have been observed in several malignant tumors. In this study, we presented a pharmacophore‐based virtual screening of a moderate database of 171 143 small molecules. A pharmacophore of LSD1 inhibitors was constructed for the first time and then used to screen the compound library combined with validated molecular docking tools followed by biochemical assays, led to the identification of 9 novel LSD1 inhibitors, showing their IC50 values in a range of 2.41–101 μm. Furthermore, compound XZ09 exhibited less inhibition against the homologous monoamine oxidase A (MAO‐A) and B (MAO‐B) displaying its moderate selectivity. Our study provides an effective virtual screening method to identify new LSD1 inhibitors and XZ09 represents a potent and selective lead compound to deserve further optimization for the treatment of LSD1 overexpressing cancers.